Effectiveness of Social Assistance Distribution in Reducing Poverty in Gunung Seteleng Village, North Penajam Paser Regency - Marlina, Marlina; Samad, Abdul; Mujahid, Mujahid (Journal of Management and Administration Provision, 2024)
This study aims to analyze the effectiveness of social assistance distribution in reducing poverty, identify factors that influence the effectiveness of distribution, and evaluate the implementation of social assistance programs so that they are more targeted and have a long-term impact on the poor in Gunung Seteleng Village. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Informants in this study consisted of the Village Head, RT Head, and the community receiving social assistance. Data were analyzed inductively by emphasizing the meaning and deep understanding of the phenomenon being studied. The results of the study indicate that the distribution of social assistance in Gunung Seteleng Village has not been effective in significantly reducing poverty. The assistance received is temporary and does not touch the root of the poverty problem. The main inhibiting factors include inaccurate targeting, weak coordination between institutions, lack of data accuracy, and minimal empowerment and supervision programs. Integration between social assistance and economic empowerment programs is needed so that poverty reduction goals can be achieved sustainably.